Civil Servants Performance Analysis of Education, Youth And Sports Department in Bantul District 2017 - Surya Jaya Abadi; Muhammad Eko Atmojo; Helen Dian Fridayani (Universitas Muhammadiyah Tangerang, 2019)
Bureaucratic reform is an effort to reform and change fundamentally in a system of governance that involves institutional aspects (organization), management (business process) and human resources apparatus to realize good governance. In Law No. 5 of 2014 concerning the State Civil Apparatus where has a function as the executor of public policy and public servants. The lack of civil servants within the Bantul Regency Government, such as teachers, health workers and technical personnel, are caused by the presence of retired employees and the enactment of the civil servants candidate (CPNS) moratorium policy which causes the workload (ABK) figures of an organization and employees to be heavier than before which can affect public service quality. The method used in this study is descriptive qualitative. The results showed that the performance of civil servants in the Education, Youth and Sports department was very good, besides that the arrangement of work plans was also in accordance with the standards of the organization. However, there are some obstacles, especially in the timeliness of completing assignments, and the ideas or initiatives of civil servants in delivering ideas are still lacking. Meanwhile, the factors that influence civil servants performance in carrying out their tasks are lack of human resources, the presence of seniority and the lack of awareness of ASN about the importance of implementing education and training.